Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional dan Kecerdasan Spiritual terhadap Tingkat Pemahaman Akuntansi Mahasiswa Kota Batam - Pakpahan, Asmita Florentina; Tobing, Vargo Christian L. (Jurnal Ilmiah Wahana Pendidikan, 2023)
Accounting education in tertiary institutions is focused on teaching students so they can have a career as a professional accountant who has expertise in accounting. Understanding the science of accounting requires knowledge of the basics of accounting. The basis of accounting is used as a guide in understanding the practices and theories related to accounting. This study aims to determine the influence of intellectual intelligence, emotional intelligence and spiritual intelligence can affect accounting understanding. This research was conducted at the Batam State Polytechnic accounting study program and Batam International University. This sampling technique used purposive sampling and a sample of 295 students was obtained from the 2018, 2019, 2020, 2021 and 2022 batches. The data analysis technique implemented was multiple linear regression. Data was obtained by distributing questionnaires and applying a Likert scale. The measurement of the independent variable of intellectual intelligence is carried out by the ability to solve problems, verbal intelligence and practical intelligence. Emotional intelligence with self-knowledge, self-control, motivation, empathy, and social skills. Spiritual intelligence with being flexible, high self-awareness, ability to face and take advantage of suffering, ability to deal with various problems, indifference in causing unnecessary harm, quality of life inspired by vision and values, tendency to view holistically, tendency to ask questions and have the convenience of working against convention. Measurement of understanding of accounting through understanding of journals, ledgers, summarizing in the trial balance, making adjusting journal entries, and preparing financial reports. The results of this study state that intellectual intelligence, emotional intelligence, and spiritual intelligence have a significant effect on accounting comprehension.